Climate-Agriculture-Modeling and Decision Tool (CAMDT): A software framework for climate risk management in agriculture. (September 2017) - Han, Eunjin; Ines, Amor V.M.; Baethgen, Walter E.
Abstract: Seasonal climate forecasts (SCFs) have received a lot of attention for climate risk management in agriculture. The question is, how can we use SCFs for informing decisions in agriculture? SCFs are provided in formats not so conducive for decision-making. The commonly issued tercile probabilities of most likely rainfall categories i.e., below normal (BN), near normal (NN) and above normal (AN), are not easy to translate into metrics useful for decision support. Linking SCF with crop models is one way that can produce useful information for supporting strategic and tactical decisions in crop production e.g., crop choices, management practices, insurance, etc. Here, we developed a decision support system (DSS) tool, Climate-Agriculture-Modeling and Decision Tool (CAMDT), that aims to facilitate translations of probabilistic SCFs to crop responses that can help decision makers adjust crop and water management practices that may improve outcomes given the expected climatic condition of the growing season. Highlights: A decision support tool, CAMDT, was developed to link tercile-based seasonal climate forecasts with DSSAT crop model. CAMDT's graphical user-interface allows easy comparisons of different "what-if" scenarios. Two different methods were used to downscale seasonal climate forecasts to daily weather sequences.